Right-Wing Political Movements in Russia at Beginning of 20th Century: Relation to Armed Forces - A. A. Ivanov (Научный диалог)
The attitude of Russian right-wing parties and unions to the problems of combat readiness, recruitment, organization, training and education of the contingent of the armed forces of the Russian Empire is considered. Attention is paid to the place of the armed forces in the program settings of right-wing political movements, to the identification and interpretation by the Black Hundreds and nationalists of crisis phenomena in the army and navy, their attitude to the politicization of command staff. Particular attention is paid to the attitude of the right to the issues of modernization of the army and navy. New sources are being introduced into scientific circulation, allowing a more complete picture of the views of the right on the country’s armed forces. It is noted that the right saw in the armed forces not only a guarantor of the security, sovereignty and power of the empire, protection from external and internal enemies, but also the most important institution designed to preserve and transmit military traditions, which for the Black Hundreds and nationalists were inextricably linked with loyalty to Orthodoxy, autocracy and Russian people. It is shown that monarchism, conservatism, nationalism and anti-Semitism, characteristic of the right, are also reflected in their views on the armed forces.